2014
DOI: 10.3109/15569527.2014.888077
|View full text |Cite
|
Sign up to set email alerts
|

Povidone iodine in the treatment of adenoviral conjunctivitis in infants

Abstract: Conjunctival irrigation with 2.5% povidone iodine is effective in the treatment of adenoviral conjunctivitis in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…A review of the references and citations did not yield any additional articles. Thirty-two studies were included in the analysis; of these, 11 had a methodological quality level of 1 or 2 (details of the included studies appear in eTable 1 in the Supplement). These studies included 24 case series, 5 randomized clinical trials, 1 nonrandomized comparative trial, and 2 cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…A review of the references and citations did not yield any additional articles. Thirty-two studies were included in the analysis; of these, 11 had a methodological quality level of 1 or 2 (details of the included studies appear in eTable 1 in the Supplement). These studies included 24 case series, 5 randomized clinical trials, 1 nonrandomized comparative trial, and 2 cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…In healthy newborns, 1.25% PI was as effective as 2.5% in reducing the number of colony-forming units 40 and 2.5% PI decreased adenoviral conjunctivitis. 41 Carrim et al demonstrated that a 3 min treatment with PI decreased the number of positive cultures in patients 42 and a 10% treatment reduced the number of colony-forming units in patients undergoing cataract surgery. 43 The optimum time and concentration of PI to prevent infections is unknown, however, 5% PI decreases bacterial load significantly more than 1% PI in vivo, while in vitro studies indicate the opposite is true with lower PI concentrations appearing to decrease bacterial load more than higher concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Also some authors found povidone iodine 2.5% as an effective treatment in AVC [19]. We used the same treatment methodology during the course of AVC.…”
Section: Discussionmentioning
confidence: 99%